Risk associated with immediate implant at mandibular canine and premolars: a cone beam computed tomography (CBCT) study - Kirthiga Rameswaran; Aminah Mohd Shariff; Lim, Daniel (Penerbit Universiti Kebangsaan Malaysia, 2021)
With the evolution of implant dentistry, immediate implantation remains a challenge especially in achieving a good primary stability with avoidance of complications such as nerve injuries and lingual perforations. This study was aimed to determine the risks of nerve injury and lingual perforation following virtual implant placement at mandibular canines, mandibular first premolars and mandibular second premolars using cone beam computed tomography (CBCT) scans. From the total of 771 CBCT scans screened, 100 CBCT scans were included. Measurements were made based on the cross-section of the study teeth, that were mandibular canine, first premolar and second premolar, to obtain the distance between root apex and nerve canal as well as risk of nerve injury. A virtual implant was then placed at each site to assess the risk of lingual perforation. Generally, the distance between root apex and nerve was less than 6 mm and the highest risk of nerve injury was observed at second premolar (79.6%) followed by first premolar (45.3%) and canine (23.4%). Risk of lingual perforation following immediate implant placement was between 0.7-1.5%. The risk of nerve injury was considerably high due to insufficient root apex to nerve canal distance while the risk of lingual perforation was low.